MICROTIA: A COMPREHENSIVE ANALYSIS OF EPIDEMIOLOGY, PATHOGENESIS, MODERN DIAGNOSTIC METHODS AND RECONSTRUCTIVE TREATMENT (European Journal of Interdisciplinary Research and Development, 2025)
Background: Microtia is a congenital developmental anomaly characterized by hypoplasia of the structures of the outer ear, often combined with atresia of the auditory canal and middle ear defects. The problem is interdisciplinary in nature, affecting the functional (hearing) and aesthetic aspects, which necessitates a comprehensive approach. Aim: To conduct a detailed review of current data on the prevalence, etiopathogenesis, classifications, diagnostic algorithms and treatment options for microtia, with an emphasis on a comparative analysis of surgical techniques and their long-term outcomes. Materials and methods: A systematic literature search was conducted in the PubMed, Scopus, Web of Science, Cochrane Library, and Russian Science Citation Index databases for the period 2000–2023. Meta-analyses, randomized controlled trials, large cohort studies, systematic reviews, and clinical guidelines met the selection criteria. Data on epidemiology, genetics, imaging techniques, audiological examination protocols, surgical reconstruction techniques and their effectiveness were analyzed. Results: The prevalence of microtia varies from 0.83 to 17.4 per 10,000 births, showing geographic and ethnic variations. The etiology is multifactorial, involving genetic (TCOF1, HOXA2, SIX2 genes) and teratogenic factors (retinoid intake, maternal diabetes). Diagnosis is based on physical examination using the Marx-Aguilar or Weerda classifications, mandatory pure-tone audiometry, impedance, ABR, and high-resolution CT of the temporal bones to assess anatomy and plan surgery. The “gold standard” of reconstruction is recognized as the three-stage autoplasty with autocartilage according to Brent or the two-stage Nagata technique, which ensures durability and stability of the result (patient satisfaction >85%). An alternative technique using porous polyethylene (Medpor) demonstrates comparable aesthetic results in the short term, but is associated with a higher risk of implant exposure (up to 15%) and requires impeccable microsurgical execution. Hearing-improving surgeries (canaloplasty, tympanoplasty) are performed after reconstruction of the auricle and require careful selection of patients based on CT criteria. Conclusion: Successful management of a patient with microtia requires coordinated work of a team consisting of a plastic and maxillofacial surgeon, an otolaryngologist-audiologist, a geneticist, a speech therapist and a psychologist. The choice of reconstruction method should be individual, based on the degree of deformation, age, donor resources of the patient, technical capabilities of the clinic and informed choice of the family.Prospects are associated with the development of tissue engineering and 3D bioprinting of cartilage structures.